Procyclical Fiscal Policy : Shocks, Rules, and Institutions; A View From Mars - Manasse, Paolo (IMF Working Papers; Working Paper ;, 2006)
This paper assesses the roles of shocks, rules, and institutions as possible sources of procyclicality in fiscal policy. By employing parametric and nonparametric techniques, I reach the following four main conclusions. First, policymakers' reactions to the business cycle is different depending on the state of the economy-fiscal policy is "acyclical" during economic bad times, while it is largely procyclical during good times. Second, fiscal rules and fiscal responsibility laws tend to reduce the deficit bias on average, and seem to enhance, rather than to weaken, countercyclical policy. However, the evidence also suggests that fiscal frameworks do not exert independent effects when the quality of institutions is accounted for. Third, strong institutions are associated to a lower deficit bias, but their effect on procyclicality is different in good and bad times, and it is subject to decreasing returns. Fourth, unlike developed countries, fiscal policy in developing countries is procyclical even during (moderate) recessions; in "good times," however, fiscal policy is actually more procyclical in developed economies.